Evaluation of Information System Framework and Suitability of Technology Tasks on the Continuing Intention to Adopt E-Learning Systems - Fiati, Rina; ., Widowati; Kusumo Nugraheni, Dinar Mutiara (DESIDOC Journal of Library & Information Technology, 2025)
This research aims to propose an information system framework that explores the relationship between perceived suitability and adoption factors in e-learning systems. The evaluation framework is built on previous information system success models and identifies the relationship between people, organisations, and technology task suitability. This research introduces a new framework by combining the dimensions of service quality, satisfaction, user behavior, and system accuracy. A quantitative approach was chosen to produce data objectively, used a questionnaire survey and structural equation modeling to analyse 782 respondents consisting of 643 students and 139 active lecturers at a university in Central Java, Indonesia. The results show that the relationship between humans and technology significantly affects sustainability intentions and perceived impacts. Meanwhile, people and organisations demonstrate attitudes and skills that positively impact system adoption. The findings of the study confirm the validity of the use of the proposed e-learning website application assessment model. Information and service quality variables influence user satisfaction and system use. Organisational elements influence user satisfaction and benefit value with level of significant 0.05 . In addition, a methodology was found that integrates human factors, organisational environment and technology suitability to assess system satisfaction and effectiveness.